2003
DOI: 10.1002/bjs.4120
|View full text |Cite
|
Sign up to set email alerts
|

l-Erythro-methoxamine is more potent than phenylephrine in effecting contraction of internal anal sphincter in vitro

Abstract: L-Erythro-methoxamine is four times more potent than phenylephrine and is a possible treatment for incontinence. Trials are under way to examine the efficacy of L-erythro-methoxamine in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…With this in mind, Jones et al [7] compared phenylephrine with a number of methoxamine isomers in vitro and concluded that 1R,2S-methoxamine was four times as potent as phenylephrine, potentially reducing the concentration of drug required to produce a clinically desirable effect. In 2005, Nisar et al compared perianal, intra-anal and intra-rectal application of 1 ml 1R,2S-methoxamine gel in concentrations of 0.3-3% and found a significant rise in MARP with intra-anal and intra-rectal but not perianal application.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…With this in mind, Jones et al [7] compared phenylephrine with a number of methoxamine isomers in vitro and concluded that 1R,2S-methoxamine was four times as potent as phenylephrine, potentially reducing the concentration of drug required to produce a clinically desirable effect. In 2005, Nisar et al compared perianal, intra-anal and intra-rectal application of 1 ml 1R,2S-methoxamine gel in concentrations of 0.3-3% and found a significant rise in MARP with intra-anal and intra-rectal but not perianal application.…”
Section: Discussionmentioning
confidence: 97%
“…NRL001 (1R,2S-methoxamine hydrochloride) is a stereoisomer of methoxamine hydrochloride that is being developed for the treatment of faecal incontinence as an agent that increases sphincter tone. 1R,2S-methoxamine is four times more potent than phenylephrine [7]. Local intra-anal application of 1R,2S-methoxamine is associated with increases in MARP in healthy volunteers and patients with faecal incontinence [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Methoxamine is a highly selective α 1 agonist, with almost no action at α 2 ‐ or β‐adrenoceptors24, and does not gain access to the central nervous system. A study of isolated porcine IAS demonstrated that the synthetic enantiomer L ‐erythro methoxamine has fourfold greater potency in eliciting a contraction than phenylephrine or racemic methoxamine25. The contractile response to L ‐erythro methoxamine is mediated via α 1 ‐adrenoceptors, and it is likely that most of the α 1 ‐agonist activity of racemic methoxamine resides in the enantiomer.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results for the IAS have been reported previously. 20 Cumulatively applied carbachol, used to activate muscarinic receptors, contracted urethra with a maximum at 3 Â 10 À4 M but relaxed IAS with a maximum at 10 À3 M. This strongly suggests that the innervation of the two tissues is different.…”
Section: Discussionmentioning
confidence: 93%